The Effect of Inquiry Training Learning Model for Student Science Process Skills - Hendra Waldi Sihaloho; Sahyar Sahyar; Mariati P Simanjuntak (Universitas Negeri Medan, 2018)
This study aims to determine the effect of learning inquiry training model to the students' science process skills (KPS). Quasi experimental research was conducted using pretest-posttest control group design. The sample in this research is X-1 class as experiment class and X-2 class as control class chosen by probability sampling. The instrument used is the KPS obtained by written test and observation. Data in this research is analyzed by using t test. The results showed that there was influence of inquiry training model and conventional learning model to the students' science process skill where the students taught with inquiry training got better than conventional.